Advancing Electric Vehicle Safety and Adoption in Indonesia: Insights from Global and Local Perspectives - Dimas Akmarul Putera; Nofias Fajri; Tania Alda (Engineering Proceedings)
Electric vehicles (EVs) are central to global efforts in reducing carbon emissions and transitioning toward sustainable transportation. This literature review emphasizes the critical role of safety in advancing EV adoption in Indonesia by drawing insights from global advancements and addressing local challenges. Key findings highlight that while EVs promise significant environmental benefits, safety concerns, such as battery thermal runaway risks and structural reliability in diverse road and climatic conditions, remain significant barriers. Issues such as battery safety, including thermal runaway risks, and the reliability of structural designs in Indonesia’s diverse road and climatic conditions are pivotal. Globally, advancements in battery management systems (BMS), crash-resistant vehicle designs, and autonomous driving technologies provide effective pathways to mitigate these safety risks. Locally, the development of safety standards tailored to tropical climates and robust infrastructure is essential. Leveraging Indonesia’s natural resources, such as nickel, offers opportunities to produce safer and cost-effective batteries. Additionally, policy frameworks like Presidential Regulation No. 55/2019 must prioritize safety measures, including rigorous testing, recycling protocols, and public education. This study concludes by advocating for an integrated approach that combines technological innovation, enhanced safety features, and supportive policies to accelerate EV adoption in Indonesia. Future research should focus on improving safety technologies, lifecycle assessments, and renewable energy integration to ensure the long-term success of EV adoption in the country.